The Influence of Advertising Spending and Monetary Promotion on Brand Loyalty with Brand Identification as a Mediating Variable for the Mie Sedaap Brand - Djawa, Getrudis Hendrina Maramba; Lukitaningsih , Ambar; Ningrum, Nonik Kusuma (Dinasti Publisher, 2025)
This research aims to analyze the influence of advertising spending and monetary promotion on brand loyalty, with brand identification serving as an intervening variable for the Mie Sedaap brand. This study used a quantitative approach with 150 respondents, and SPSS was used for data analysis. The findings indicate that both advertising spending and monetary promotion have a positive and significant effect on brand loyalty. Furthermore, advertising spending and monetary promotion also positively and significantly influence brand identification. Lastly, brand identification is found to have a positive and significant effect on brand loyalty.